English Teacher Experience in Using Digital Media during Teaching English at Islamic Junior High School in Pasuruan - Hanna Patriotic Kirani; Ermawati Zulikhatin Nuroh (English Department FKIP Universitas Muhammadiyah Surabaya Indonesia, 2025)
Using digital media to teach English is very varied, but the most important thing is how to use digital media. Furthermore, an English teacher can have new experiences using digital media in the classroom. This research aims to explore English teachers' experiences using digital media while teaching English. The research object is the experience of English teachers using digital media in teaching English at Muhammadiyah 4 Gempol Junior High School. This research uses a qualitative case study approach. The data was collected through observation and interviews with the research subjects, especially English teachers at Muhammadiyah 4 Gempol Junior High School. The observation and interview sheet will be used as the research instrument in this study. This research is expected to provide information about teachers' experiences in teaching with digital media and a reference for future research.